Uwarunkowania decyzji wyborczych na przykładzie wyborów prezydenckich w 1995 roku - Drozdowski, Rafał; Pawłowska, Barbara (Wydział Prawa i Administracji UAM, 1997)
The article is founded on empirical results of the research programme named "Matters of Poles - Autumn '95" (realized in 1995 - 1996). The research was referred to a very large poll comprising 814 respondents throughout Poland. The specificity of situation in Poland consists nowadays in the fact that although the awareness of the society is being dominated by economic interests (as most important regulators of everyday adaptive strategies) - the sphere of political behaviour and of electoral preferences is subject to rules of other kind. Political choices are determined by values which are confessed, then by auto-identification on the "left-right" scale, but most of all by past political biography of the electorate itself.
Conditions of electoral decisions on the example of presitential elections of 1995